Light, sex and sporophytes: aspects of the ecology of Pallavicinia lyellii in an unusual habitat. (1st October 2020) - Callaghan, Des A.; Lyons, Justin; Bosanquet, Sam
ABSTRACT: Introduction. This study investigated the ecology of Pallavicinia lyellii in a mire habitat dominated by Molinia caerulea, including potential abundance, frequency of sexes and sporophytes, and characteristics of the light climate beneath the herbaceous canopy. Methods. Within the study site (Cors Fochno, Wales, UK), P. lyellii was surveyed in March 2020. Abundance was measured as counts of colonies, their sexual composition was recorded, and number of sporophytes determined. Photosynthetic photon flux density (PPFD) was measured beside colonies, paired with measurements taken 1 m above the colony under open sky. A hemispherical sky image was captured, and sun tracks overlaid, at a representative colony. Results. Fifty-eight colonies of P. lyellii occurred, in two populations. One population exhibited male bias, a low portion of sterile colonies and a relatively large number of sporophytes. The other exhibited female bias, a high portion of sterile colonies and very few sporophytes. Molinia caerulea blocked ca. 91% of PPFD, and light at colonies of P. lyellii was consistently low (mean PPFD = 29 μmol m −2 s −1 ). Hemispherical photography shows no direct sunlight may reach P. lyellii during October–February and suggests during the remainder of the year such events could be extremely limited. Conclusions . Molinia mire can support large populations of P. lyellii and will be important for its future survival in Britain. Research is needed to quantify the microhabitat favoured by the liverwort, such as relationship to light, hydrology and water chemistry, and how these can be affected by management.